The ClujUAV student competition: A corridor navigation challenge with autonomous drones⁎This event was financially sponsored by Accenture and Elektrobit; by the Romanian National Authority for Scientific Research, CNCS-UEFISCDI, project number PN-III-P1-1.1-TE-2016-0670; by the European Commission via grant agreement no. 9/2018, Co4AIR - Computers, Cognition and Communication in Control: A strategIc paRtnership" project funded through the Erasmus+ KA2 scheme; and by a HAS Bolyai Scholarship. Issue 2 (2020) - Sándor, Csanád; Pável, Szabolcs; Wieser, Erik; Blaga, Andreea; Boda, Péter; Fülöp, Andrea-Orsolya; Ursache, Adrian; Zöld, Attila; Kopacz, Anikó; Lázár, Botond; Szabó, Károly; Tasnádi, Zoltán; et al.
Abstract: We describe a novel student contest concept in which an unmanned aerial vehicle (UAV or drone) must autonomously navigate a straight corridor using feedback from camera images. The objective of the contest is to promote engineering skills (related to sensing and control in particular) among students and young professionals, by means of an attractive robotics topic in an exciting competition format. The first edition of this contest was organized in Cluj-Napoca, Romania on October 19th 2019. Teams from industry and academia competed, with an overall positive experience. We outline the challenge and scoring rules, together with the technical solutions of the teams, and close with a summary of the results and points to improve for the next editions.